Target-mediated self-assembly of DNA networks for sensitive detection and intracellular imaging of APE1 in living cells - Zhou, Xue-Mei; Zhuo, Ying; Yuan, Ruo; Chai, Ya-Qin (Chemical science (Cambridge), 2023)
Herein, giant DNA networks were assembled from two kinds of functionalized tetrahedral DNA nanostructures (f-TDNs) for sensitive detection and intracellular imaging of apurinic/apyrimidinic endonuclease 1 (APE1) as well as gene therapy in tumor cells. Impressively, the reaction rate of the catalytic hairpin assembly (CHA) reaction on f-TDNs was much faster than that of the conventional free CHA reaction owing to the high local concentration of hairpins, spatial confinement effect and production of giant DNA networks, which significantly enhanced the fluorescence signal to achieve sensitive detection of APE1 with a limit of 3.34 × 10 −8 U μL −1 . More importantly, the aptamer Sgc8 assembled on f-TDNs could enhance the targeting activity of the DNA structure to tumor cells, allowing it to endocytose into cells without any transfection reagents, which could achieve selective imaging of intracellular APE1 in living cells. Meanwhile, the siRNA carried by f-TDN1 could be accurately released to promote tumor cell apoptosis in the presence of endogenous target APE1, realizing effective and precise tumor therapy. Benefiting from the high specificity and sensitivity, the developed DNA nanostructures provide an excellent nanoplatform for precise cancer diagnosis and therapy. We designed two functionalized tetrahedral DNA nanostructures (f-TDN1 and f-TDN2), which could assemble into giant DNA networks triggered by APE1, achieving sensitive detection and intracellular imaging of APE1 as well as gene therapy.